Distributed electrical network modelling approach for spatially resolved characterisation of photovoltaic modules. Issue 5 (1st July 2014) - Wu, Xiaofeng; Bliss, Martin; Sinha, Archana; Betts, Tom; Gupta, Rajesh; Gottschalg, Ralph
Abstract : Distributed electrical modelling and simulation plays an important role in investigating local operating points and the overall power generation of photovoltaic (PV) modules. A PV module is a three‐dimensional device in which inhomogeneities can cause a non‐uniform performance and hence, electrical mismatches which consequently reduce the overall power generation. Distributed modelling and simulation can be used to identify local electrical properties and their impacts on the power output. In this study, a flexible, distributed electrical network modelling approach is presented. The proposed approach introduces a hierarchical architecture built up from the diode model‐based sub‐cell level to the module level. A PV‐oriented nodal analysis solver is developed to enable the spatially resolved quantitative analysis of electrical operating points by given local properties including irradiance, temperature, series resistance, shunt resistance and ideality factor. The approach has been verified by PSpice software. The case studies have shown that this modelling and simulation tool can be used to analyse spatially resolved characterisation results and to predict global and distributed operating points under different conditions.